Risk analysis of gold processing in artisanal and small-scale gold mining in Bolaang Mongondow Regency, North Sulawesi, Indonesia - Margareth Rosalinda Sapulete; Hefni Effendi; Etty Riani; Machfud Machfud (Journal of Degraded and Mining Lands Management, 2023)
Gold processing at artisanal and small-scale gold mining (ASGM) in Indonesia is inherently risky due to the high severity and likelihood of accidents causing serious injury. The objectives of this study were to identify hazards, assess risks, and determine risk control measures in the ASGM location at Imandi Village, East Dumoga District, Bolaang Mongondow Regency, North Sulawesi Province. The method used was Hazard Identification Risk Assessment and Risk Control (HIRARC). The determination of work stages and identification of hazards was carried out through observation at 14 ASGM units and interviews with 14 informants consisting of 6 mining workers and 8 ASGM business owners. The risk assessment was carried out by observing and interviewing 8 experts as informants selected from health and environmental scientists, various offices of the Government Bolaang Mongondow Regency, and non-government institutions. The results showed that the stage of gold processing work in ASGM consists of 13 sources of hazards that can pose 16 risks. The obtained risk assessment results showed that 19% were low risk, 31% moderate risk, 25% high risk, and 25% very high risk caused by exposure to mercury through the gold ore burning process with a risk value of 25. The identified risk control measures were PPE (personal protective equipment) 43%, administrative controls 14%, engineering controls 14%, substitution 21%, and elimination 7%. Realistic risk controls that can be applied in ASGM are a combination of administrative controls and PPE.